Foundation Macromedia Dreamweaver MX 2004 - Grannell, Craig; Powers, David; McLachlan, George (Friends of Ed, 2004)
For additional information concerning changes to PHP since publication of this title, please refer to the notes at the foot of this page. Dreamweaver MX 2004 is the latest version of Macromedia's world-class visual web-authoring tool, which includes powerful yet easy-to-use database integration. Unlike many other books, Foundation Dreamweaver MX 2004 focuses on both sides of coin - no matter what your background, this book will give you a solid foundation in graphic design and layout issues as well as full training in the powerful server-side and database integration features that Dreamweaver offers. The truth is that in today's climate database integration is no more of an extra than faultless visual design, and this book is here to guide you through this new world, covering dynamic scripting with PHP and the popular MySQL database. This book covers: Site design and layout principles Using templates and Cascading Style Sheets to create advanced site designs Adding interactivity to pages with PHP script Setting up PHP and MySQL to create powerful dynamic database-driven applications Even if you are already using Dreamweaver and want to extend your skills towards dynamic content, interactive and engaging to your visitors. Or maybe you're a developer who wants to make the most of this sophisticated productivity tool and take full advantage of the renowned Dreamweaver interface to improve your workflow. Foundation Dreamweaver MX 2004 gives you the essential grounding that you'll need in the all-important design context. Whether a complete novice or a past user, after reading this book, you'll be fluent in the full breadth of the powerful functionality that Dreamweaver MX 2004 has to offer. This book presents a unique learning curve backed up by solid real-world case studies and tutorials.